Coding Whiteness and Racialization: Living in the Space as an Insider-Outsider - Karaman, Nuray (Journal of International Students, 2022)
This study analyzes whiteness from the perspectives of “politic of location” to understand how it has changed and applied across the globe, rather than ignoring the relevancy of white supremacy for some geographies that have a racially homogenous population. The first part of the article interrogates my personal experiences of whiteness in Turkey which has a racially homogenous population. In Turkey, my experiences with whiteness were not as a result of directly having white bodies, but rather by being a part of the dominant culture, nation, religion, and language. The second part of this study discusses my experiences of whiteness in the United States. I highlight the different ways in which I experienced whiteness that had to do with my position as a Muslim Turkish woman in racially diverse America. In this autoethnography, by showing my relations and experiences within the discourse of whiteness and racialization of Muslims, I show how whiteness has significantly different meanings in different locations, and how whiteness’s ideology affects people’s experiences through local and global power relations.